Anticoagulation Treatment in Cancer-Associated Venous Thromboembolism: Assessment of Patient Preferences Using a Discrete Choice Experiment (COSIMO Study) - Picker, Nils; Lee, Agnes Y.; Cohen, Alexander T.; Maraveyas, Anthony; Beyer-Westendorf, Jan; Mantovani, Lorenzo G.; Abdelgawwad, Khaled; Fatoba, Samuel; Thate-Waschke, Inga-Marion; Bach, Miriam; Wilke, Thomas (Thrombosis and Haemostasis, 2020)
Introduction Clinical guidelines recommend anticoagulation therapy for the treatment of cancer-associated venous thromboembolism (VTE), but little is known about preferences. Therefore, the objective of this discrete choice experiment (DCE) was to elucidate patient preferences regarding anticoagulation convenience attributes.Methods Adult patients with cancer-associated VTE who switched to direct oral anticoagulants were included in a single-arm study (COSIMO). Patients were asked to decide between hypothetical treatment options based on a combination of the following attributes: route of administration (injection/tablet), frequency of intake (once/twice daily), need for regular controls of the international normalized ratio (INR) at least every 3 to 4 weeks (yes/no), interactions with food/alcohol (yes/no), and distance to treating physician (1 vs. 20 km) as an additional neutral attribute. DCE data were collected by structured telephone interviews and analyzed based on a conditional logit regression.Results Overall, 163 patients (mean age 63.7 years, 49.1% female) were included. They strongly preferred oral administration compared with self-injections (importance of this attribute for overall treatment decisions: 73.8%), and a treatment without dietary restrictions (11.8%). Even if these attributes were less important (7.2% and 6.5%, respectively), patients indicated a preference for a shorter distance to the treating physician and once-daily dosing compared with twice-daily intake. “Need for regular controls of INR at least every 3 to 4 weeks” showed no significant impact on the treatment decision (0.7%).Conclusion This study showed that treatment-related decision making in cancer-associated VTE, assuming comparable effectiveness and safety of anticoagulant treatments, is predominantly driven by “route of administration,” with patients strongly preferring oral administration.
Keywords: anticoagulation; patient preferences; treatment-related decision making; discrete choice experiment; cancer-associated venous thromboembolism